Importance of E/e’ and BNP for early detection of late cardiotoxicity in long-term follow-up of childhood hematologic cancer survivors: a retrospective cross-sectional study - Yuri Okazoe-Hirakawa; Kimikazu Yakushijin; Keiji Kurata; Sakuya Matsumoto; Hiroya Ichikawa; Rina Sakai; Taku Nose; Shiro Kimbara; Yoshiaki Nagatani; Taiji Koyama; Yumiko Inui; Yohei Funakoshi; et al. (Cardio-Oncology)
Abstract Background Childhood cancer survivors (CCS) often develop late complications after their primary disease is cured. Cardiovascular disease is one of the most frequent and serious complications that significantly affects prognosis and quality of life. Early detection and appropriate intervention are expected to improve their prognosis. However, the risk factors for late cardiotoxicity in CCS are not well defined, and biomarkers that can detect cardiac dysfunction prior to the development of heart failure have not yet been established. Methods Medical records of childhood hematologic cancer survivors referred to our department for transitional care between January 2016 and October 2023 were reviewed for this cross-sectional study. The relationships between the most recent cardiac function at the review and history of cancer treatment were analyzed. Results This study included 34 patients and the median elapsed time since cancer diagnosis was 16.5 years (range, 5–30 years). None of the patients had symptomatic cardiac complications. The E/e’ ratio was significantly higher in survivors with a history of hematopoietic stem cell transplantation (HSCT) than in those who did not undergo HSCT (median, 8.4% vs. 6.25%, P = 0.040), while no intergroup differences were observed in ejection fraction (EF), global longitudinal strain (GLS), or the brain natriuretic protein (BNP) level. In addition, the E/e’ ratio was positively correlated with years elapsed since cancer diagnosis (ρ = 0.38, P = 0.034). While there was no clear correlation between years since cancer diagnosis and the BNP level in the overall cohort, a strong correlation was found in patients with a history of HSCT (ρ = 0.73; P < 0.01). No significant differences were observed in EF, E/e’ ratio, GLS, and BNP level by cumulative anthracycline dose or history of chest irradiation. Conclusions In this study, no patient had late symptomatic cardiac complications. However, in those who had survived for a long time since their cancer diagnosis, particularly those with a history of HSCT, there were significant elevations in the E/e’ ratio and the BNP level. Continuous follow-up is required to determine whether these abnormalities lead to symptomatic cardiotoxicity and whether they serve as useful markers for the early detection of cardiac complications.